Perancangan Alat Ukur Penilaian Kinerja di PT X dengan Menggunakan Balanced Scorecard - Brillianty, Silvia Floretta; Bendatu, Liem Yenny (Jurnal Titra, 2013)
PT X is one of the companies in Surabaya which producing coconut oil and palm oil. This study was conducted to generate a design of performance measurement in PT X, based on the balanced scorecardâs four perspectives. The design focused on the Department of Plant 1 and Plant 2, which are the core department in the production section. Balanced scorecard covers the measurement of strategic design, program matrix design and Key Performance Indicators for each level positions. The measurement of strategic design is divided into three parts, namely the srategic measurement for PT X in general, Department of Plant 1 and Department of Plant 2. Program matrix consists on current programs and also suggestions on new programs to achieve the companyâs target. The Key Performance Indicator covers four levels of the existing positions in each Department of Plant 1 and Department of Plant 2, which are Section Head, Deputy Section Head, Supervisor and Operator.